2022
DOI: 10.5812/intjssh.122590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verbal Encouragements on Selected Measures of Physical Fitness and Subjective Effort Perception in Young High School Students

Abstract: : This study aimed to examine the effects of verbal encouragements (VE) on linear sprint speed, jump height, change of direction (CoD) speed, and subjective perception of effort among high school students. Twenty-three high school male students volunteered to participate in this study (age = 19.70 ± 1.06 years). Participants were evaluated during two separate sessions (first session with VE and second session without VE) in a randomized order. The teacher provided VE during each physical test. Jump height [squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…In other words, the lack of significance of RPE values could be explained by the fact that VETS and VESS play a role in distracting sensory and physical signals during exercise. However, the result of the present study diverges with previous studies which reported that the psych-physiological characteristics of football players can be influenced by the presence of a physical education teacher (i.e., VE) [ 2 , 16 , 19 ]. For example, Selmi et al [ 3 ] discussed the value and efficacy of VE in raising internal intensity during repeated agility speed training (RAS).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In other words, the lack of significance of RPE values could be explained by the fact that VETS and VESS play a role in distracting sensory and physical signals during exercise. However, the result of the present study diverges with previous studies which reported that the psych-physiological characteristics of football players can be influenced by the presence of a physical education teacher (i.e., VE) [ 2 , 16 , 19 ]. For example, Selmi et al [ 3 ] discussed the value and efficacy of VE in raising internal intensity during repeated agility speed training (RAS).…”
Section: Discussioncontrasting
confidence: 99%
“…Research on affective valence is increasingly using the FS, which measures the positive affective response induced by participating in a certain activity [ 16 , 35 , 36 , 37 ]. In this investigation, the perceived positive affective score, which was assessed following the VETS condition, was higher than the scores that decelerated following the VESS and control conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, these authors advocate for the utilization of VE to enhance sports and motor performance. According to several studies, PVE and CVE have been shown to have positive effects on physical performance and motivation [ 28 , 29 , 30 ]. These tools are crucial for improving the teaching-learning process and motivating athletes during physical exercise [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these challenges include the time-consuming nature of the testing process and the unavailability of suitable locations with the required characteristics due to various geographical, social, and economic reasons. On the other hand, the results of performance tests may be affected by the internal and external motivational factors of the athlete being tested, as well as the gender of the tester, and somatic characteristics may be affected [ 11 ]. In addition, although it is thought that the physical fitness levels of healthy individuals and the performance test results will be parallel, individuals who are underweight can also perform better than those with overweight/obesity, similar to individuals with a normal body weight [ 12 ].…”
Section: Introductionmentioning
confidence: 99%